The Effects of Online and Offline Marketing on Consumer Behavior in the UAE Telecommunication Industry - Makovská, Simona; Cook, Gina, 1970-; Lhotáková, Markéta, 1971-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2016)
The master thesis is concerned with the impact of online and offline marketing. These effects are researched in the conditions of United Arab Emirates and its telecommunication industry. The goal of the thesis is to identify the effects of offline and online marketing tools on consumer behavior in the UAE telecommunication industry. The main added value of the thesis is brought through primary research that was conducted on the sample of 100 respondents living in the UAE. The results show the increasing importance of online marketing tools and stress the significance of synergic effects of implementing adequate online and offline marketing tools.
Vedoucí práce: Gina Cook
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses